Membongkar Kedalaman Kriminalitas: Analisis Ilmiah Pembunuhan Terhadap Orang Tua Tiri - Rafika Handayani; Muh. Fadli Faisal Rasyid; Amir Amir (Jurnal Litigasi Amsir, 2024)
This normative legal research employs a statutory approach and utilizes a case study from a court in Parepare City. Primary, secondary, and tertiary legal materials serve as sources. The qualitative prescriptive analysis focuses on the crime of murder under Article 340 of the Criminal Code, as evidenced in Decision Number: 52/Pid.B/2022/Pn Pre. The public prosecutor presented three indictments, with the first proven against the defendant, Sahrul Alias Callu Bin Sirajuddin. The panel of judges, in Verdict Number: 52/Pid.B/2022/Pn Pre, declared the defendant guilty of premeditated murder, sentencing him to 7 years in prison. The verdict considered various factors, including prosecutor demands, trial facts, and elements fulfillment, alongside aggravating and mitigating circumstances.